Strategic Exploration of Construction Management Practices at Alok Construction - Agarwal, Yash Alok (ATLAS SkillTech University, 2025)
The internship report titled "Strategic Exploration of Construction Management Practices at Alok Construction" provides a comprehensive overview of my enriching experience as a Construction Management Intern at Alok Construction, a leading company in the industry. The report encapsulates the valuable insights and practical knowledge I gained during this internship, which I completed over the summer as part of my second-year MBA curriculum at Atlas Skilltech University. Throughout the internship, I actively participated in various aspects of construction management, including financial analysis, project documentation, budget management, site inspections, and ensuring safety compliance. Under the guidance of Dr. Vinima Gambhir, my esteemed faculty mentor, I navigated the complexities of construction projects and bridged the gap between theoretical concepts and real-world applications. The report elaborates on the significance of this hands-on experience, highlighting its impact on my professional growth and aligning my academic knowledge with the demands of the modern construction landscape. This executive summary aims to provide a glimpse into the detailed findings and reflections shared in the subsequent sections of the report, enabling readers to comprehend the value of this transformative internship experience at Alok Construction.
Project Report on Strategic Exploration of Construction Management Practices at Alok Construction (2023-2025) Under the Guidance of Prof. Vinima Gambhir
Keywords: valuable insights; Strategic; Construction Management; financial analysis; project documentation; budget management